Ecology is a priority - (:unkn) unknown (Харків : ХНУ імені В.Н. Каразіна, 2023)
Видання містить матеріали, які стосуються сучасних екологічних проблем та шляхів їх вирішення, прикладних екологічних досліджень та екологічних наслідків війни.

The publications contain the proceedings which address the modern ecological problems and ways of their solution, applied ecological research and ecological consequences of war.
Keywords: green infrastructure; urban landscape; environment; pollution; impact; dangerous zones; explosive objects; damages; environmental safety; global warming; protected areas; erosion; nature reserve; optimization; landscape; sustainability; comfort weather